The Migrate project: the challenges of operating a transmission grid with only inverter‐based generation. A grid‐forming control improvement with transient current‐limiting control. Issue 5 (21st November 2017) - Denis, Guillaume; Prevost, Thibault; Debry, Marie‐Sophie; Xavier, Florent; Guillaud, Xavier; Menze, Andreas
Abstract : Renewable generation is mainly connected through converters. Even if they provide more and more ancillary services to the grid, these may not be sufficient for extremely high penetrations. As the share of such generating units is growing rapidly, some synchronous areas could in the future occasionally be operated without synchronous machines. In such conditions, system behaviour will dramatically change, but stability will still have to be ensured with the same level of reliability as today. To reach this ambitious goal, the control of inverters will have to be changed radically. Inverters will need to move from following the grid to leading the grid behaviour, both in steady state and during transients. This new type of control brings additional issues on converters that are addressed in this study. A solution is proposed to allow a stable operation of the system together with a limited solicitation of inverters during transients.